(untitled) (Terr@ Plural, 2021)
The landscape of Rio de Janeiro manifest a controversial relationship between urbanization and geodiversity, which can be unveiled through geotouristic tours around the city. The local geodiversity imposed limits and provided possibilities for the occupation of the city, as observed in the transformations during its urbanization and in the presence of rocks and fossils of different origins in the local buildings and monuments. In order to stimulate the conservation and dissemination of our Natural and Cultural Heritage, the Geotouristic Tour by the Historic Center of the City of Rio de Janeiro was structured to highlight the relationships between geodiversity and urbanization through an integration of Geosciences, History and Arts.